The effectiveness of public finances provided to public library services in the Czech Republic - Pichová, Simona (Vysoké učení technické v Brně, 2016)
This article aims to provide an overview of the efficiency of allocated funding for the provision of public library services. The article deals with monitoring the impact of individual variables on the dependent var-iable - the amount of return on in-vestment (ROI). The article works with the values obtained in the project "We will calculate ROI," which took place in 2015 in the Czech Republic in cooperation with the Munici-pal Library in Prague and Pardubice University with the support of the Ministry of Culture of the Czech Republic. Data obtained in this project was drawn up by the cost-benefit analysis. The impact of individual determinants of the amount of ROI will be assessed by multiple regression analysis and cluster analysis. The article aims to determine, depending on the amount of selected indicators ROI. Estimates show a sig-nificant determinant which ones are important and have an impact on the value of ROI. The influence of regional indicators and values regarding specific libraries. The article accounted the ROI of 36 libraries in the Czech Republic and their comparison for the years 2012 and 2014. Libraries were divided into groups based on similarity of values of significant indicators. This is the first research in the Czech Republic, which was made in measuring the value of public libraries, which were determined to ROI on specific li-braries for such a large sample of observations. Monitoring the impact of regional indicators points to the fact that the amount of the ROI does not affect the location of the library, the library or success does not depend on the county in which the library is located. Libraries can be divided into groups that differ sig-nificantly and according to this distribution can select different methods of public funding.
Efektivnost veřejných financí poskytovaných na služby veřejných knihoven v České republice
Keywords: public library; public services; efficiency; public investments; cost-benefit analysis; veřejná knihovna; veřejné služby; veřejné investice; metoda nákladů a přínosů